INVESTIGASI GETARAN PADA PERUBAHAN KONSTRUKSI KAMAR MESIN - Viko Ahmad Fernando (2022)
Physical damage to ships is strongly influenced by vibration, such as ship construction and the level of comfort when the ship is operating. To investigate the resulting vibration, it is necessary to consider the dynamic force acting due to the effect of the excitation frequency on the natural frequency. This study uses the finite element method, which is a structural analysis method using a numerical approach to obtain an approximate solution of a problem until the results of the research show that the engine room construction in this drawing design is strong and seaworthy. In this case, data obtained from ship resistance of 149.8 kN from PT Dok & Perkapalan Kodja Bahari. The engine power requirement to fight the resistance is obtained at 2027,189 KW based on the results of the analysis, where the engine on KM SABUK NUSANTARA XX produces 1030 x 2 KW. In the geometry of this model, only the basic depiction of the ship is carried out and the maximum stress value is 107.41 Mpa. The safety factor value (SF > 1) is 2.187. The value of longitudinal vibration on the ship is still below the permissible ABS standard, which is 0.09 < 0.022 T_o.